Accounting Paradigm from a Sociological Study Perspective - Susilo, Tri Achmad Budi; Hidayat, Taufiq; Tjahjono, Dwi; Kuswandono, Andi; Sjachriatin, Elia; Revia, Tria (Universitas Kristen Cipta Wacana, 2024)
This article aims to provide a conventional understanding of accounting, descriptions related to functionalism and positivist, sociological perspectives or scientific paradigms as well as relevant philosophical foundations underlying conventional understanding. This study seeks to explore the differences in several sociological perspectives that develop in studying or conducting studies on accounting as a direct impact of differences in sociological perspectives of the organization. The methodology used in this study is qualitative with secondary data methods mainly through bibliometric research obtained from journals or supporting articles. Accounting is a multiparadigm subject and accounting studies are currently in transition. The perspective of social sciences, especially sociology, has the potential to open a wider space for accounting researchers or future researchers to examine the issues or problems of accounting science from other perspectives that have been